2013
DOI: 10.1371/journal.pone.0064420
|View full text |Cite
|
Sign up to set email alerts
|

MYC Deregulation in Gastric Cancer and Its Clinicopathological Implications

Abstract: Our study investigated the relationship between MYC alterations and clinicopathological features in gastric cancers. We evaluated the effect of MYC mRNA expression and its protein immunoreactivity, as well as copy number variation, promoter DNA methylation, and point mutations, in 125 gastric adenocarcinoma and 67 paried non-neoplastic tissues. We observed that 77% of the tumors presented MYC immunoreactivity which was significantly associated with increased mRNA expression (p<0.05). These observations were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
69
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 57 publications
12
69
2
3
Order By: Relevance
“…Numerous studies of gene expression in human gastric mucosa use GAPDH as the reference gene (58,59), despite the knowledge that GAPDH is upregulated in stomach cancer (24). The present study demonstrated that GAPDH was highly variable between groups, and was therefore not recommended as a reference gene.…”
Section: Discussioncontrasting
confidence: 58%
“…Numerous studies of gene expression in human gastric mucosa use GAPDH as the reference gene (58,59), despite the knowledge that GAPDH is upregulated in stomach cancer (24). The present study demonstrated that GAPDH was highly variable between groups, and was therefore not recommended as a reference gene.…”
Section: Discussioncontrasting
confidence: 58%
“…In another study, MYC amplification significantly correlated with MYC mRNA levels and MYC immunoreactivity, suggesting that MYC CNV indeed contributes to its overexpression in GC. 95 In mucinous gastric carcinoma, c-MYC amplification was correlated with greater invasion depth and advanced tumor stage, while these differences were not found in non-mucinous gastric carcinomas, suggesting that c-MYC amplification in mucinous gastric carcinoma may be a genetic alteration contributing to the frequent presentation of advanced stage of MGC. 96 The POU5F1B gene (POU domain class 5 transcription factor 1B, the OCT4 pseudogene), which is located on human chromosome 8q24 near MYC, 97 is frequently amplified in GC.…”
Section: Chromosomementioning
confidence: 85%
“…MYC es un protooncogén que se activa por mutaciones, reordenamientos genéticos, inserciones y/o duplicaciones, todos estos cambios se encuentran con frecuencia en CG (de Souza et al 2013, Leal et al 2011, Calcagno et al 2009. En cánceres como endometrio, páncreas y pulmón se encuentran mutaciones en MYC, las más frecuentes son de cambio de sentido (80,3%), seguidas de mutaciones silenciosas (19,7%).…”
Section: Gen Myc (V-myc Avian Myelocytomatosis Viral Oncogene Homolog)unclassified
“…En cánceres como endometrio, páncreas y pulmón se encuentran mutaciones en MYC, las más frecuentes son de cambio de sentido (80,3%), seguidas de mutaciones silenciosas (19,7%). En CG-TI no se reportan mutaciones para este gen (Sanger Institute 2011), las mutaciones se asocian, principalmente, con CG-TD (9%) y con metástasis (tabla 1) (de Souza et al 2013). Por otro lado, MYC se encuentra sobreexpresado con mayor frecuencia en CG-TI que en CG-TD, 45% frente al 10%, respectivamente (Calcagno et al 2009, Leal et al 2011), y con poca frecuencia (11%) en metaplasia intestinal (Calcagno et al 2010).…”
Section: Gen Myc (V-myc Avian Myelocytomatosis Viral Oncogene Homolog)unclassified
See 1 more Smart Citation